FTIR Spectroscopic Imaging of Wear and Corrosion Products within Joint Capsule Tissue from THR Patients - Liu, Songyun (J Biomed Mater Res B Appl Biomater, 2019)
Implant debris generated by wear and corrosion is a prominent cause of joint replacement failure. This study utilized Fourier Transform InfraRed spectroscopic Imaging (FTIR-I) to gain a better understanding of the chemical structure of implant debris and its impact on the surrounding biological environment. Therefore, retrieved joint capsule tissue from five total hip replacement patients was analyzed. All five cases presented different implant designs and histopathological patterns. All tissue samples were formalin-fixed and paraffin-embedded. Unstained, 5μm thick sections were prepared. The unstained sections were placed on BaF(2) windows and deparaffinized with xylene prior to analysis. FTIR-I data were collected at a spectral resolution of 4 cm(−1) using an Agilent Cary 670 spectrometer coupled with Cary 620 FTIR microscope. The results of study demonstrated that FTIR-I is a powerful tool that can be used complimentary to the existing histopathological evaluation of tissue. FTIR-I was able to distinguish areas with different cell types (macrophages, lymphocytes). Small, but distinct differences could be detected depending on the state of cells (viable, necrotic) and depending on what type of debris was present (polyethylene (PE), suture material and metal oxides). Although, metal oxides were mainly below the measurable range of FTIR-I, the infrared spectra of tissues exhibited noticeable difference in their presence. Tens of micrometer sized polyethylene particles could be easily imaged, but also accumulations of submicron particles could be detected within macrophages. FTIR-I was also able to distinguish between PE debris, and other birefringent materials such as suture. Chromium-phosphate particles originating from corrosion processes within modular taper junctions of hip implants could be identified and easily distinguished from other phosphorous materials such as bone. In conclusion, this study successfully demonstrated that FTIR-I is a useful tool that can image and determine the biochemical information of retrieved tissue samples over tens of square millimeters in a completely label free, non-destructive, and objective manner. The resulting chemical images provide a deeper understanding of the chemical nature of implant debris and their impact on chemical changes of the tissue within which they are embedded.